2022
DOI: 10.1371/journal.ppat.1010275
|View full text |Cite
|
Sign up to set email alerts
|

Beta human papillomavirus 8 E6 allows colocalization of non-homologous end joining and homologous recombination repair factors

Abstract: Beta human papillomavirus (β-HPV) are hypothesized to make DNA damage more mutagenic and potentially more carcinogenic. Double strand breaks (DSBs) are the most deleterious DNA lesion. They are typically repaired by homologous recombination (HR) or non-homologous end joining (NHEJ). HR occurs after DNA replication while NHEJ can occur at any point in the cell cycle. HR and NHEJ are not thought to occur in the same cell at the same time. HR is restricted to cells in phases of the cell cycle where homologous tem… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
15
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
5
1

Relationship

3
3

Authors

Journals

citations
Cited by 8 publications
(16 citation statements)
references
References 72 publications
1
15
0
Order By: Relevance
“…Instead, they delay the resolution of RAD51 foci, suggesting that the repair complexes that form may be non-functional [ 84 ]. Supporting this idea, some of the RAD51 foci that form in cells expressing HPV8 E6 occur in G1 phase, when they are unlikely to be efficiently resolved due to the lack of a homologous template [ 86 ]. HPV38 E6 that weakly binds to p300 did not significantly decrease BRCA1 or BRCA2 expression.…”
Section: Beta Hpv and Genomic Instabilitymentioning
confidence: 99%
See 4 more Smart Citations
“…Instead, they delay the resolution of RAD51 foci, suggesting that the repair complexes that form may be non-functional [ 84 ]. Supporting this idea, some of the RAD51 foci that form in cells expressing HPV8 E6 occur in G1 phase, when they are unlikely to be efficiently resolved due to the lack of a homologous template [ 86 ]. HPV38 E6 that weakly binds to p300 did not significantly decrease BRCA1 or BRCA2 expression.…”
Section: Beta Hpv and Genomic Instabilitymentioning
confidence: 99%
“…To address this knowledge gap, a recent effort tracked the persistent HR and NHEJ foci found in earlier work [ 84 , 99 ]. This work found that HPV8 E6 caused HR factors (RPA70 and RAD51) to be recruited to sites of stalled NHEJ repair [ 86 ]. NHEJ and HR are intrinsically incompatible.…”
Section: Beta Hpv and Genomic Instabilitymentioning
confidence: 99%
See 3 more Smart Citations